Digital technologies, Fourth Industrial Revolution (4IR) & Global Value Chains (GVCs) nexus with emerging economies' future industrial innovation dynamics - Brighton Nyagadza; R. Pashapa; A. Chare; G. Mazuruse; P. K. Hove (Cogent Economics & Finance, 2022)
The advent of the Fourth Industrial Revolution (4IR) has the potential to transform emerging economies to another developmental echelon by increasing productivity and improving future fluidity of innovation across various industries. Predictively, 4IR in emerging economies will come with newest technologies that are disruptive. This technological innovation will cause changes not only in industries and business but also in societies in general. The current article is based on the Preferred Reporting Items for Systematic Literature Review and Meta-Analysis (PRISMA) of secondary data sources, mainly peer reviewed reputable journal articles. The purpose is to draw conclusions and to identify the research gaps. Results depicted that the key challenge is for the emerging economies to establish ways of engaging themselves into Global Value Chains (GVCs) that are dynamic in nature. Future researchers are encouraged to consider alternative methodologies to examine 4IR and GVCs nexus with emerging economies' within a longitudinal research design. Systematic literature review in the current article is based on a structural analysis methodology to frame the categories of the major analysis in combination with scientific rigour to a broad and complex problem. The current scientific research study contributes to theory, practice and future research directions.
Keywords: 330; innovation; Fourth Industrial Revolution (4IR); futures studies; Global Value Chains (GVCs); new digital technologies; sustainable development